ORAL HEALTH BEHAVIOR AND KNOWLEDGE OF ADULT DIABETIC PATIENTS REGARDING ORAL COMPLICATIONS OF DIABETES MELLITUS; A DESCRIPTIVE CROSS SECTIONAL STUDY IN TERTIARY CARE HOSPITAL OF RAWALPINDI - Javaid, Dr. Nigarish; Rahman, Dr. Mahmood Ur; Azam, Dr. Naila; Pervaiz, Dr. Farrah; Tariq, Dr. Kiran; Younis, Dr. Fazeela; Mahmood, Dr. Humaira (Pakistan Armed Forces Medical Journal, 2019)
Objective: To determine the knowledge of diabetic patients regarding oral complications of diabetes mellitus in tertiary care hospital of Rawalpindi. To determine the oral health behavior including their oral health care practices, attitudes and utilization of dental services of diabetic patients in tertiary care hospital of Rawalpindi.Study Design: Descriptive cross-sectional study.Place and Duration of Study: Combined Military Hospital, Rawalpindi. 6 months from July 18 to Dec 18.Material and Methods: Non probability convenient Sampling was used on 344 diabetic patients who visited outpatient medical department of CMH, Rawalpindi. The data was collected by using a semi structured questionnaire developed with the help of literature review. Frequency and percentages were computed and chi square was used to find associations between demographics status and knowledge about oral complications of diabetes mellitus. Age, duration of diabetes, education, family history and mode of treatment were the independent variables and knowledge, behavior, attitude and utilization of dental services were dependent variables.Results: Of the 344 participants recruited in the study 62% (214) were females, 67% (230) had a family history of diabetes, 55% (188) had more than 10 years of schooling and 24% (82) had received oral health education. 86% used tooth brush and fluoridated paste to clean their teeth. 48% (165) brushed only once daily. Of the 211 patients who did use an interdental cleaning aid, 168 preferred a tooth pick. Only 10 percent (35) had knowledge about periodontitis as the most frequently encountered disease in diabetics, many did not visit a dental facility at least once a year. Chi square test showed a significant association between education and knowledge about oral diseases and frequency of tooth brushing (p-value